Digitalization of the german civil procedure (Acta Judicial Journal, 2022)
The digitisation of the German civil procedure has been taking place gradually since the beginning of the 2000s. Thus, this paper examines the legislative iter that has led to an all-encompassing attempt at digitisation, which will materialise in the next few years. The main digitisation proposals circulating in German practice and procedural theory are therefore analysed, with special consideration of the implications of digitisation with regard to the general principles of German civil procedure.
Keywords: Digitalization; civil procedure; inmediacy; publicity; Germany